PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT KARYA SATRIA BEKASI - Eka Risti; Kurniawati Mulyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
The purpose of this research is to comprehend the influence of leadership and compensation toward employee performance of PT. Karya Satria Bekasi. The used method is analysis descriptive method. Population in this research is 71 office employees and field employees. Data analysis technique exerts double regression with SPSS Program. If it is observed partially, the result is that leadership and compensation variable affect significantly to employee performance of PT. Karya Satria Bekasi, and jointly leadership and compensation affect the performance. Leadership contribution is 50,1%, and the rest 49,9 % is influenced by another factor. Leadership and compensation variable can be used in regression model to predict employee performance.